Hi, I've been practising predicate calculus I am struggling with this question and as I have seen below it would be good if the response is in Fitch-style. Thank you very much.

It is proving:

(∀x. P(x)) -> (∀y. P(y))

I know that this involves generalisation etc. but I am quite sure about how to do it (probably assuming a ? if a is one of the x's)

As far as I know, I've learnt Universal and existential instantiation, universal and existential generalisation (and probably natural deduction rule in predicate logic).

Thank you very much for your support!

Regards

Sekaiyoma